EVALUASI SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) PADA PENGGUNAAN BAHAN KIMIA BERBAHAYA DI AGROINDUSTRI PAKAN TERNAK SURABAYA - Yayok Suryo Purnomo; Muhammad Yusuf Rasyidin (EnviroUS, 2022)
Surabaya's Animal Feed Agroindustry is a massive enterprise withinside the subject of animal feed that ensures the great of feed from the start of the method to packaging. The system of the use of chemical substances to enhance the great of the ensuing product. The application of the OH&S Management System needs to be evaluated in the control of hazardous chemicals. The method used aims to implement an OH&S Management System in accordance with PP RI number 50 of 2012 concerning the Control of Hazardous Chemicals. Because the company is still implementing Kepmenaker Kep. 187/MEN/1999. The results of the evaluation are based on PP RI number 50 of 2012 that the company only meets 2 sub-criteria, namely there are material safety data sheets and occupational safety and health signs. So, the company is still fixing 3 more sub-criteria in the implementation of OH&S Management System.